2000
DOI: 10.1046/j.1526-4610.2000.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypnic Headache: Another Indomethacin-Responsive Headache Syndrome?

Abstract: Hypnic headache syndrome is a benign, recurrent, late-onset headache disorder that occurs exclusively during sleep. Lithium has been reported to be an effective treatment, but the side effects of this medication are sometimes prohibitive, particularly in the elderly. Other drugs have been reported to be effective in this disorder, including caffeine, flunarizine, and verapamil. Recently, indomethacin has been reported to effectively suppress hypnic headaches. We report the response of seven patients with hypni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 15 publications
3
44
1
4
Order By: Relevance
“…A good response was also noted with lower doses, even 150 mg at bedtime [8]. Out of the patients treated with lithium, this drug was discontinued in 5 cases [1, 3133] despite its efficacy, due to significant adverse effects. Poor tolerability to lithium is not rare, mainly in elderly patients.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…A good response was also noted with lower doses, even 150 mg at bedtime [8]. Out of the patients treated with lithium, this drug was discontinued in 5 cases [1, 3133] despite its efficacy, due to significant adverse effects. Poor tolerability to lithium is not rare, mainly in elderly patients.…”
Section: Treatmentmentioning
confidence: 99%
“…The efficacy of indomethacin is of special interest because this drug is also effective in paroxysmal hemicrania and hemicrania continua [36]. It has been suggested that indomethacin may be helpful in those patients whose HH attacks are unilateral [31]. It was shown to be effective in extremely variable doses, ranging from 25 mg to 150 mg/day.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Lithium is the most effective drug for prophylactic treatment of HH. Indomethacin has been suggested to be helpful in unilateral HH [7]. We report a case of relapsing–remitting variety of HH in an adolescent who showed complete response to indomethacin.…”
Section: Introductionmentioning
confidence: 97%